2009
DOI: 10.1016/j.micinf.2008.11.007
|View full text |Cite
|
Sign up to set email alerts
|

Leishmania donovani lipophosphoglycan inhibits phagosomal maturation via action on membrane rafts

Abstract: Lipophosphoglycan (LPG), the major surface glycoconjugate on Leishmania donovani promastigotes, is crucial for the establishment of infection inside macrophages. LPG comprises a polymer of repeating Galβ1,4Manα-PO 4 attached to a lysophosphatidylinositol membrane anchor. LPG is transferred from the parasite to the host macrophage membrane during phagocytosis and induces periphagosomal F-actin accumulation correlating with an inhibition of phagosomal maturation. The biophysical properties of LPG suggest that it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
47
0
1

Year Published

2011
2011
2025
2025

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(52 citation statements)
references
References 31 publications
(48 reference statements)
4
47
0
1
Order By: Relevance
“…In the case of Leishmania, it was shown that this parasite alters several of the functional properties of phagosomes, including the ability of this organelle to fuse with late endosomes and lysosomes (61). The inhibition of membrane fusion requires that the parasite surface molecule lipophosphoglycan (LPG) be targeted to membrane rafts at the phagosomal membrane (12). LPG is also known to alter the generation of oxygen superoxides, and the integrity of the actin network surrounding phagosomes (62).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the case of Leishmania, it was shown that this parasite alters several of the functional properties of phagosomes, including the ability of this organelle to fuse with late endosomes and lysosomes (61). The inhibition of membrane fusion requires that the parasite surface molecule lipophosphoglycan (LPG) be targeted to membrane rafts at the phagosomal membrane (12). LPG is also known to alter the generation of oxygen superoxides, and the integrity of the actin network surrounding phagosomes (62).…”
Section: Discussionmentioning
confidence: 99%
“…Recent data indicated that two phagosomal protein complexes, V-ATPase and NADPH oxidase may use membrane microdomains as assembly platforms (11). Furthermore, the potential involvement of phagosome microdomains in innate immunity was highlighted by the finding that at least two unrelated pathogens, the Gram-negative bacteria Brucella and the intracellular parasite Leishmania donovani, target phagosome lipid rafts as a strategy to evade host-defense mechanisms (12)(13)(14). Hence, the molecular characterization of the detergent-soluble and -insoluble fractions isolated from phagosomes should provide unique insights into the mechanisms used by pathogens to alter the functional properties of this organelle.…”
mentioning
confidence: 99%
“…The bestcharacterized Syt in phagocytosis is the lysosomal Syt VII, which regulates Ca 2+ -dependent exocytosis of lysosomes (Martinez et al, 2000) and the delivery of lysosomal membrane to the phagosome (Czibener et al, 2006). More recently, we identified Syt V as a recycling endosomeassociated protein recruited to the forming phagosome, and we showed that this exocytosis regulator controls the phagocytic process (Vinet et al, 2008).Upon contact between promastigotes and macrophages, LPG transfers from the parasite surface to the nascent phagosome membrane (Tolson et al, 1990), where it disrupts existing lipid microdomains and alters the formation of these structures after promastigote internalization (Dermine et al, 2005;Winberg et al, 2009). One consequence of LPG membrane insertion is the exclusion of Syt V .…”
mentioning
confidence: 73%
“…These virulence factors can also be transferred to the macrophages by parasite-produced exosomes (Silverman and Reiner 2010). When promastigote enters into the phagosome, LPG inserts itself into lipid rafts and inhibits phagosome-lysosome fusion (Winberg, Holm et al 2009). The inhibition of fusion is accompanied by accumulation of periphagosomal filamentous actin (F-actin) near lipid microdomains.…”
Section: Host Cells For Leishmania Parasitesmentioning
confidence: 99%